PLANNING TOOLS AND THEIR EFFECTIVENESS IN REACHING ORGANIZATIONAL GOALS: A STUDY OF GOVERNMENT AGENCIES IN SOUTH-SOUTH NIGERIA - Okonkwo, Nnenna Ruth; Ijeoma , Samuel Chinedu (Ayden International Journal of Law, Political Science, and Administration, 2024)
The study examined the relationship between planning and achievement of organizational goal. This correlational study was conducted as a cross-sectional survey. The population size of this study is one hundred (3,000) staff members of three (3) functional and service delivery government owned institutions in South-South, Nigeria. The study therefore shows that there is a significant relationship between effective planning and achievement of organizational objective. It was concluded that planning is necessary for the survival of an organization. This study however, recommends that organizations should accord priority to planning, set realistic goals, establishment of long term objective, this has to be measurable and specific, the development of strategic plans and its implementation, making adequate environmental analysis , suitable organizational structure and a host of other measures for effective strategic planning kin to organizations